(untitled) (Ágora de Heterodoxias, 2020)
The following article compiles the experiences that a group of researchers of the Autonomus University of Nayarit (UAN-México and State University of Distance Education (UNED-C.R.) jointly apply on a group of students who participate on a program aiming to develop research skills. From a distance-learning perspective, this paper explains in three chapters how research topic were chosen, as well as their teaching activities and the curricular research elements curricular. Finally, to close up, the paper enlist a series of final considerations and good practices.